Prevalence and factors associated with antepartum depression among adolescent women in the assin north district of Ghana: a cross-sectional study - Hannah Amoquandoh Asante; Shadrach Tetteh Boyetey; Ebenezer Essaw; Christopher Amoah Nyame; Bertha Mante; Louisa Dziwornu; Paul Okyere (BMC, 2024)
Abstract Background Globally, depression is a leading cause of disease-related disability among women. In low-and-middle-income countries (LMICs), the prevalence rate of antepartum depression is estimated to range between 15% and 57% and even higher in adolescent antepartum women. Although a number of studies have shown that depression is common in adolescent pregnancies and has a prevalence rate between 28% and 67% among adolescent mothers, there currently exists no literature on depression among adolescent pregnant women in Ghana. The study aimed to determine the prevalence of antepartum depression and identify the factors associated with it among pregnant adolescent women. Methods A quantitative cross-sectional study design was adopted by randomly recruiting 220 adolescent pregnant women visiting antenatal clinics in five selected health facilities in five communities in the Assin North District of Ghana. Data were collected using the Edinburgh Postnatal Depression Scale (EPDS). Data analysis was performed using Stata version 14. Both descriptive and inferential analyses were performed. A chi-square analysis was conducted to identify the association between independent and dependent variables. A multivariate logistic regression analysis was carried out to identify the independent variables that were significantly associated with the dependent variable. In all analyses, p-values ≤ 0.05 were deemed statistically significant at a 95% confidence interval. Results The results indicated prevalence of depression was 38.6% using the EPDS cut-off ≥ 13. Respondents who were cohabiting were less likely to experiencing antepartum depression compared to those who were single (AOR = 0.36, 95% CI: 0.20-0.64, p = 0.001). Also, Respondents who had completed Junior High School had a lower likelihood of experiencing antepartum depression compared to those who had no formal education (AOR = 0.19, 95% CI: 0.05-0.76, p = 0.019). Respondents who perceived pregnancy-related items to be costly had higher odds of experiencing antepartum depression (AOR = 2.05, 95% CI: 1.02-4.12, p = 0.042). Lastly, adolescent pregnant women who reported that pregnancy-related items are costly were likely to experience antepartum depression compared to those who did not report such costs (AOR = 2.12, 95% CI: 1.20-3.75, p < 0.001). Conclusion The results of this study highlight the importance of a multi-pronged strategy for combating antepartum depression in adolescents and improving the overall health and well-being of pregnant adolescents. Considering that adolescence is a transitional period occasioned by several bio-psycho-social challenges, setting up systems to ensure that young girls are motivated and supported to stay in school will enhance their economic prospects and improve their standards of life while providing psycho-social support will benefit their health and general well-being.